A Comparison of Higher Education System between China and Ukraine - Shatska, Oksana (Kultura-Społeczeństwo-Edukacja, 2014)
This article compares the higher education systems between China and Ukraine, discusses some important peculiarities of the two, and points out the differences between the two. The purpose is to help us get a better understanding of the two countries’ higher education systems and to improve the educational exchange and collaboration of the two countries. Special attention is paid to structures of two universities, their facilities, rules of admission, the organization of studying process and some approaches, and levels of acknowledgements by governments which show us the differences and similarities between the two.